Konsep Sosialisme Islam menurut Sayid Quthb - Asnawiyah Asnawiyah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
This paper attempts to trace how the concept of social thinking introduced by Sayyid Qutb, better known by the concept of Islamic socialism. Socialism is one of the tenets that wants the Elimination of social inequalities in society. This teaching is done in an effort to bridge between the luxury life with the life of the lower classes, so that gave birth to life balance in a public order. Observing this, then social systems analyze three important aspects, namely: first, the public relations of various systems; Secondly, the normal situation or a situation of balance, in line with normal conditions, and third, all systems perform normal system to reintegration. Thought Sayid Qutb give new shades of thought in the aspect of community development in Islam. He sought to correlate to the thinking that is introduced by the West and the Islamic version of the social aspect of teaching.